COMMERCIAL IDENTITY FOR HARDWARE STORE IN CIUDAD DEL ESTE - Mario Barboza Benitez , Edgar; Elizabeth Miltos Romero, Jazmin; Gabriel Zavala Escobar , Teo (Revista Gênero e Interdisciplinaridade, 2023)
The commercial identity is defined as what the organization represents for its consumers, that is, those essential features that differentiate them from others, it can also be considered as the set of meanings that the public associates with an organization; and the reputation is defined as the judgment that is made on the organization, this work focuses specifically on the item of hardware stores with a problem based on the lack of a commercial identity, which leads to the presence of difficulties related to positioning within From the market. In this way, an investigation is presented that applies the quantitative paradigm, compiling information related to the strategies used by companies to achieve commercial identity. The survey technique was used for various companies in the hardware sector located on Av. San José in Ciudad del Este, in order to respond to the initially proposed objectives. The main results of the research work demonstrated the little knowledge of the use of branding by the owners of the companies and it is necessary to promote strategies that help to build the brand’s personality.